Role of cell surface matrix metalloproteinases - Itoh, Y; Seiki, M (2001)
Membrane-type matrix metalloproteinase (MT-MMP) is a subgroup of MMP family proteinases. To date, six members of MT-MMP have been discovered by cDNA cloning. They are expressed on the cell surface by anchoring to the plasma membrane. Four of them are transmembrane-type, and two are glycosylphosphatidylinosotol (GPI) anchor-type. They are synthesized as a zymogen and activated by pro-hormone convertases intracellularly to appear on the cell surface as an active form. Among MT-MMPs, MT 1-MMP is the most characterized proteinase and its importance has been implicated in cancer invasion, angiogenesis, and bone morphogenesis. It acts on ECM either directly by itself or indirectly by activating proMMP-2. As MT-MMPs are expressed on the cell surface and degrade pericellular ECM, it modifies the signals given by ECM. Thus, their roles are likely to be directly connected to cell functions, and this is the character of MT-MMPs over other soluble-type MMPs.